Association between history of childbirth and chronic, functionally significant back pain in later life - Michelle Zhang; Corinne Cooley; Maisa S. Ziadni; Ian Mackey; Pamela Flood (BMC, 2023)
Abstract Background Back pain is more prevalent among women than men. The association with sex could be related to pregnancy and childbirth, unique female conditions. This association has not been thoroughly evaluated. Methods Using a retrospective cohort design, we evaluated the relationship between history of childbirth on the prevalence and severity of functionally consequential back pain in 1069 women from a tertiary care pain management clinic. Interactions among preexisting, acute peripartum, and subsequent back pain were evaluated as secondary outcomes among the parous women using logistic and linear regression as appropriate. Results The women who had given birth had a higher risk for functionally significant back pain compared to women who had not given birth (85% vs 77%, p < 0.001, Risk Ratio 1.11 [1.04-1.17]). The association was preserved after correction for age, weight, and race. Back pain was also more slightly severe (Numerical Rating Score for Pain 7[5-8] vs 6[5-7] out of 10, p = 0.002). Women who recalled severe, acute postpartum back pain had a higher prevalence of current debilitating back pain (89% vs 75%, Risk Ratio 1.19 (1.08-1.31), p = 0.001). Twenty-eight percent of acute postpartum back pain never resolved and 40% reported incomplete resolution. Conclusions A history of pregnancy and childbirth is a risk factor for chronic functionally significant back pain in women. Severe acute postpartum back pain is a risk factor for future disability suggesting that the peripartum period may provide an important opportunity for intervention. Early recognition and management may mitigate future disability. Trial registration The study was registered with clinicaltrials.gov as "Association Between Chronic Headache and Back Pain with Childbirth" (NCT04091321) on 16/09/2019 before it was initiated.